Pengaruh niat berperilaku, kecerdasan spiritual dan literasi keuangan terhadap pengelolaan keuangan keluarga - Tomi Arganata; Lutfi Lutfi (STIE Perbanas Surabaya, 2019)
Family financial managemenet is very important in fostering the family economy. This study aims to examine the effect of behavioral intentions, spiritual intelligence, and financial literacy on family financial management. It used the sample consisting of 179 financial managers of the family as the correspondents. The data were collected by questionnaires using a purposive sampling technique and convenience sampling technique. The data were analysed using Multiple Regression Analysis (MRA). The results indicate that behavioral intention and spiritual intelligence have a significant positive effect on family financial management, while financial literacy have positive but not significant impact on family financial management. The implication of this study are that family financial managers need to better internalize their religious guidelines and strengthen intentions to behave in the form of establishing financial behavior targets so that they can better realize wise and responsible financial management.